ответ:
\frac{13k-4}{3-13k}+ \frac{x}{3-13k}=1
\frac{13k-4+x}{3-13k}= \frac{3-13k}{3-13k}
\frac{13k-4+x}{3-13k}- \frac{3-13k}{3-13k} =0
\frac{13k-4+x-(3-13k)}{3-13k}=0
\frac{13k-4+x-3+13k}{3-13k}=0
\frac{26k-7+x}{3-13k}=0
\left \{ {{26k-7+x=0} \atop {3-13k \neq 0}} \right. ; \left \{ {{x=-26k+7} \atop {k \neq \frac{3}{13} }} \right. ; \left \{ {{x=7-26k} \atop {k \neq \frac{3}{13} }} \right.
ответ: если k \neq \frac{3}{13} , то x=7-26k
объяснение:
288 | 2 528 | 2
144 | 2 264 | 2
72 | 2 132 | 2
36 | 2 66 | 2
18 | 2 33 | 3
9 | 3 11 | 11
3 | 3 528 = 2⁴ · 3 · 11
1
288 = 2⁵ · 3²
НОД = 2⁴ · 3 = 48 - наибольший общий делитель
288 : 48 = 6 528 : 48 = 11
ответ: НОД (288 и 528) = 48.
ответ:
\frac{13k-4}{3-13k}+ \frac{x}{3-13k}=1
\frac{13k-4+x}{3-13k}= \frac{3-13k}{3-13k}
\frac{13k-4+x}{3-13k}- \frac{3-13k}{3-13k} =0
\frac{13k-4+x-(3-13k)}{3-13k}=0
\frac{13k-4+x-3+13k}{3-13k}=0
\frac{26k-7+x}{3-13k}=0
\left \{ {{26k-7+x=0} \atop {3-13k \neq 0}} \right. ; \left \{ {{x=-26k+7} \atop {k \neq \frac{3}{13} }} \right. ; \left \{ {{x=7-26k} \atop {k \neq \frac{3}{13} }} \right.
ответ: если k \neq \frac{3}{13} , то x=7-26k
объяснение: